Aromatically different Apiaceae spices harbour potential novel antibacterial compounds for drug repurposing against ESKAPE pathogens - Tanessri Muni; Muhammad Shahid; Shristi Prasad; Preksha Dave; Dr. Chandrajit Lahiri (Educational Administration: Theory and Practice, 2024)
Spices have been utilized over the centuries for culinary and medicinal purposes. Their usage mostly differed as per the different geographical regions and their ethnicity. While they can be of the same class, they might differ in their flavour, aroma, and therapeutic potential. Herein we have explored the widely used south, east, and southeast Asian spices of the Apiaceae family namely cumin (Cumminum cyminum) and fennel (Foeniculum vulgare) for their therapeutic potential as natural sources of drug repurposing against the infections caused by the multidrug-resistant ESKAPE pathogens. Essentially, crude extracts of fractions in a series of solvents were prepared and assessed for their preliminary antibacterial potential. All these fractions were analysed through GC-MS and the overlapping constituents were further explored. A stepwise approach of virtual screening followed by pharmacological assessment was taken bioinformatically to reveal the potential top rankers having the druggability against selected virulent proteins from the ESKAPE pathogens. Further molecular dynamics simulation affirmed the finding of top-ranking compounds with their antibacterial potentials. Earlier known as anticancer agents, these compounds hold the promise for drug repurposing from natural sources like spices against the multidrug-resistant ESKAPE pathogens.